2010
DOI: 10.3758/s13415-010-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Rostral anterior cingulate activity generates posterior versus anterior theta activity linked to agentic extraversion

Abstract: Recent research using the resting electroencephalogram (EEG) showed that posterior versus anterior theta activity (around 4-8 Hz) is consistently associated with agency, reflecting the dopaminergic core of extraversion (i.e., incentive motivation, positive emotion). Neuroimaging studies using various methodologies and experimental paradigms have converged on the anterior cingulate cortex (ACC) as a neurophysiological correlate of extraversion. The aim of the present study is integrate these lines of research b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 76 publications
5
27
1
Order By: Relevance
“…Consistent with DA-models of agency (Depue & Collins, 1999), the FzPz index and its relationship to agency are sensitive to DA (Wacker et al, 2006). Further, a source localization study suggests that the rostral anterior cingulate cortex is the primary generator of the FzPz index (Chavanon et al, 2011). Although altered rostral ACC theta and delta activity during rest has been reported in healthy subjects with anhedonic symptoms (Wacker et al, 2009), the correlation between the FzPz index and anhedonia was not significant in the present study of healthy and depressed participants.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Consistent with DA-models of agency (Depue & Collins, 1999), the FzPz index and its relationship to agency are sensitive to DA (Wacker et al, 2006). Further, a source localization study suggests that the rostral anterior cingulate cortex is the primary generator of the FzPz index (Chavanon et al, 2011). Although altered rostral ACC theta and delta activity during rest has been reported in healthy subjects with anhedonic symptoms (Wacker et al, 2009), the correlation between the FzPz index and anhedonia was not significant in the present study of healthy and depressed participants.…”
Section: Discussionsupporting
confidence: 51%
“…While agency was unrelated to feedback-evoked theta alterations, there was a negative correlation between agency and the feedback-independent FzPz index as in a number of prior studies on resting EEG . This correlation is typically most pronounced for the agency facet of extraversion (Chavanon et al, 2011;Knyazev, Bocharov, & Pylkova, 2012) and -as in the present study -always indicates enhanced relative frontal theta power in intro-versus extraverts. Consistent with DA-models of agency (Depue & Collins, 1999), the FzPz index and its relationship to agency are sensitive to DA (Wacker et al, 2006).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Intriguingly, this study showed that the source of intracerebral θ was localized within the rostral subdivisions of the ACC. The current density of θ within the rostral ACC was significantly correlated with the agentic extraversion spectrum, and had high retest stability during 5 h [30] .…”
Section: Eeg and Erpsmentioning
confidence: 94%
“…The results showed that the extraversion-related differences in the loadresponsivity pattern were reversed by sulpiride, and the effect was especially large in frontal areas. A recent EEG study was extended to the θ rhythm (4-8 Hz) to investigate the interaction between personality and cognitive performance [30] . Intriguingly, this study showed that the source of intracerebral θ was localized within the rostral subdivisions of the ACC.…”
Section: Eeg and Erpsmentioning
confidence: 99%